A NEW INSIGHT INTO THE YOUTH’S WAY OF PERSONAL BRANDING THROUGH STUDYGRAM - Anindya Widita; Yudhistya Ayu Kusumawati; Frederik Masri Gasa (Jurnal Pustaka Komunikasi, 2022)
Social media fuel youth’s creativity and provide a platform to share their identity and develop their brand. Studygram are study bloggers who utilize Instagram to post their student life, in particular studying activities. Personal brand can be developed through communicating one’s characteristic and establishing desired impression to public of one’s skill, personality, or other traits. Studygram account is an example of a way to craft personal brand. This paper aims to explain the personal branding presentation from the youth’s perspective through Instagram. Related concepts include personal branding, study bloggers, and Instagram aesthetic. Through case study qualitative approach, online observation and content analysis were used as the method to collect and analyze the data from the selected Studygram accounts. The result showed the presentation of branding from the consistent feed and content highlighting productivity through display of study items arranged neatly and appeasing visually. Other than focusing on productivity, activities in daily life were also shared through various content. Interaction with followers were seen through interactive captions to engage and share personal experience and tips in their student life to connect with the followers. Opportunity for further study includes evaluation whether Studygram affects their productivity, visual content analysis, or investigation of the content exposure of Studygram on the audience.